1998
DOI: 10.1080/1356215980030101
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge Production and Knowledge Transmission. The interaction between research and teaching at universities

Abstract: Even though the interaction between teaching and research at universities is a well-studied topic, it is difficult on the basis of available studies to draw any definite conclusions concerning the character of this relationship. This study, which is based on survey data, as well as interviews, shows that university faculty believe that their research influences their teaching and that their teaching activities have a positive effect on their teaching. They find, however, that research is more important for tea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
61
0
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(71 citation statements)
references
References 17 publications
7
61
0
3
Order By: Relevance
“…Research indicates that academics have a common belief that teaching and research are positively correlated (e.g., Smeby 1998). Smeby (1998) adds that academics also believe that research is more important for teaching than the other way round. According to Geiger (1985, pp.…”
Section: Different Views On the Teaching-research Nexusmentioning
confidence: 99%
“…Research indicates that academics have a common belief that teaching and research are positively correlated (e.g., Smeby 1998). Smeby (1998) adds that academics also believe that research is more important for teaching than the other way round. According to Geiger (1985, pp.…”
Section: Different Views On the Teaching-research Nexusmentioning
confidence: 99%
“…Como en el caso de los puestos acadé-micos, es posible que estas diferencias temáticas sean debidas a fenómenos de crecimiento donde los investigadores con una pequeña actividad incrementen más rápido su impacto científico que los autores con una gran producción. En cierto modo, se podría afirmar que los Profesores Asistentes de Ciencias de la Vida y Ciencias de la Salud consiguen la madurez científica más temprano que sus colegas de Arte y Humanidades y Ciencias Sociales; y la rápida ralentización en la actividad de los investigadores de Ciencias de la Vida y Ciencias de la Salud puede ser entendido como un signo de estabilidad, mientras que los Profesores Asistentes de Arte y Humanidades y Ciencias Sociales están aún desarrollando sus carreras (Smeby, 1998). En este sentido se podría sugerir que el esfuerzo en consolidar una carrera in Ciencias Sociales y Humanidades podría ser mayor que en el resto de áreas de investigación.…”
Section: Discussionunclassified
“…skills, including modules in which only research methods are taught (Durning and Jenkins 2005). Several authors mention the student level as a serious influence on the potential relationships; at graduate level the ties are usually closer than at undergraduate level (Durning and Jenkins 2005;Neumann 1992;Smeby 1998;Zamorski 2002). However, on the basis of observations, Colbeck (1998) found that the purpose of teaching -i.e.…”
Section: Learning Environmentmentioning
confidence: 96%
“…Additionally, the discipline is important. In undergraduate education in the social sciences and humanities the link is easier to realise, as the degree of specialisation and the rate of knowledge development are lower than in the natural sciences (Smeby 1998). A last factor that academics consider relevant is class size (Shore, Pinker, and Bates 1990).…”
Section: Learning Environmentmentioning
confidence: 99%